Utilização de esgoto doméstico primário em diferentes proporções na produção do mamoeiro - Batista, Adriana Alves (2013)
The reuse of treated domestic sewage for agricultural purposes is becoming a viable alternative in regions that suffer from the problem of water shortages, with an extra source of water and nutrients for the plants. Light of the foregoing the present work aimed to evaluate the development, yield, physicochemical qualitychemistry and microbiological the fruits of papaya tree culture irrigated with the different proportions of primary domestic sewage and water supplies in the rural settlements in Miracles Apodi-RN. The present study was conducted in the rural settlement project in the municipality of Miracles Apodi-RN. In the experiment we used two types of water, one supplies and another primary domestic sewage. The experimental design used was completely randomized of blocks with four treatments and six replications. Consisting of the following treatments: T1 (100% water supplies + 0% primary domestic sewage), T2 (67% water supplies + 33% of primary domestic sewage), T3 (33% water supplies + 67% primary domestic sewage) and T4 (0% water supplies + 100% primary domestic sewage). Only the T1 treatment has received chemical fertilization monthly. The water supply to the plants was carried out through the irrigation system localized low pressure Bubbler Irrigation System. The culture utilized in the experiment was of papaya plant group formosa, Tainung 1. Were evaluated: growth variables to the 274 (DAT) in character monthly, the physico-chemical characteristics of the fruit pulp, the quantitative characteristics and microbiological quality of the fruit. The data obtained were subjected to analysis of variance, the mean test and regression analysis. The T3 treatment (67% of domestic sewage and 33% of primary water supplies) caused significant increase in the variables, plant height and stem diameter, being superior to the other treatments. As for the number of sheets T1 (100% water supplies and chemical fertilization) the treatment was that if we obtained larger average leaf number. Irrigation with primary domestic sewage can be considered as an alternative source of fertilizer to maximize production of papaya tree provided that in the proper proportions. In relation to the physico-chemical quality of the fruits, the different proportions of primary domestic sewage did not provoke significant changes and are within the standards required for the marketing and consumption in natura. The microbiological quality of the fruit produced during the experiment is acceptable for consumption, since it It was observed the absence of Salmonella sp. and total coliform. The fruits produced in this study had a upper microbiological quality of the fruits commercialized in the municipality of Mossoró